MODELS OF LEARNING OUTCOMES ASSESSMENT OF PHYSICAL, SPORT AND HEALTH EDUCATION IN JUNIOR HIGH SCHOOL (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
AbstrakPenelitian ini bertujuan untuk menghasilkan: (1) Model penilaian hasil pembelajaran Penjasorkesdi Sekolah Menengah Pertama. Penelitian ini merupakan penelitian kualitatif. Subjekpenelitian ini adalah seluruh guru pendidikan jasmani di Sekolah Menengah Pertama KotaGorontalo yang terdiri dari dua puluh satu guru penjas. Pengumpulan data menggunakanobservasi, wawancara dan dokumentasi. Data yang dikumpulkan berupa dokumen maupundeskripsi mengenai permasalahan, hambatan dan fenomena yang terjadi dilapangan mengenaimodel penilaian hasil pemebelajaran Penjasorkes di Sekolah Menengah Pertama KotaGorontalo. Analisis data yang digunakan adalah triangulasi. Hasil penelitian menunjukanbahwa: (1) Pelaksanaan model penilaian hasil pembelajaran Penjasorkes di Sekolah MenengahPertama Kota Gorontalo masih sangat bervariasi dan tidak sesuai dengan kriteria mekanismepenilaian seperti yang tercantum dalam indikator pencapaian pada silabus. (2) Prosedurpelaksanaan penilaian hasil pembelajaran Penjasorkes belum berjalan dengan baik, sehinggamasing-masing Sekolah Menengah Pertama Kota Gorontalo mempunyai model penilaianhasil pembelajaran Penjasorkes dalam bentuk instrumen yang berbeda. Berdasarkan hasil penelitian,peneliti merekomendasikan : (1) Model prosedur penilaian hasil pembelajaran Penjasorkesyang dapat dijadikan sebagai solusi dalam pelaksanaan penilaian, (2) Model idealpenilaian hasil pembelajaran Penjasorkes sebagai solusi yang dapat digunakan dalam prosespenilaian hasil pembelajaran Penjasorkes di sekolah Menengah Pertama Kota Gorontalo. AbstractThis research aims to produce: (1) model of learning outcome assessment procedures of physical,sport and health education in Gorontalo City Junior High School, (2) Model assessmentof learning outcome for physical, sport and health education ideal in Gorontalo City JuniorHigh School. This research was qualitative. The subject of this study were all physical educationteachers in High School of Gorontalo City Junior consists of twenty-one od physicaleducation teachers. The data were collected using observations, interviews and documentation.Data collected in the form of a document or a description of the problems, obstacles andphenomena that occur in the field of outcomes assessment of learning model physical, sportand health education in Junior High School of Gorontalo City. Analysis of the data usedtriangulation. The results showed that: (1) The assessment model of physical, sport and healtheducation in Gorontalo City Junior High School was still highly variable and not accordingto the criteria of assessment mechanisms as listed in the indicators of achievement of the syllabus.(2) Procedures physical, sport and health education assessment of learning outcomeshave not been going well, so that each secondary School of Gorontalo City have physical,sport and health education learning outcome assessment model in the form of different instruments.Based on the results of the study, the researchers recommend: (1) model of learningoutcome assessment procedures for physical, sport and health education as a solution in theimplementation of the assessment, (2) Ideal assessment model of learning outcome for physical,sport and health education as a solution in the Junior High School of Gorontalo City.